Cognitive Achievement Paradox in High School Physics: Discrepancy Between Test Performance and Conceptual Understanding - Hermansyah Hermansyah; Syarif Fitriyanto; Sri Hartini; Cici Aprina; Armansyah Putra (U-Teach: Journal Education of Young Physics Teacher, 2026)
This study investigated the Cognitive Achievement Paradox in high school physics learning under conditions where high grades are accompanied by shallow conceptual understanding. A convergent-parallel mixed-methods design involved 48 11th-grade students at a public high school in Sumbawa. Data were collected through a concept test on Heat and Temperature, structured interviews, and classroom observations. Quantitative analysis using SPSS 26 showed a class mean of 89.81 (SD = 8.74), 95.8% achieved the KKM (≥75), and Shapiro–Wilk showed non-normality (W = 0.897, p < .001). However, qualitative findings revealed an inability to contextualize thermal phenomena, a reliance on memorization, and inadequate integration of simulation media. Results confirmed that calculation-based assessment systematically overestimates true understanding, threatening construct validity and scientific literacy. A quasi-experimental study testing the Simulation-Anchored Contextual Assessment model based on PhET simulations as an embedded formative assessment tool is recommended